Potent antibacterial activity of MXene-functionalized graphene nanocomposites - Mohammed Sadey, Salmi *; Usman, Ahmed *; Aslfattahi, Navid; Saidur, Rahman *; Hardy, John George; Ayaz, Anwar * (Royal Society of Chemistry, 2022)
Two dimensional (2D) nanomaterials display properties with significant biological utility (e.g., antimicrobial activity). In this study, MXene–functionalized graphene (FG) nanocomposites with Ti3C2Tx in varying ratios (FG : Ti3C2Tx, 25 : 75%, 50 : 50%, and 75 : 25%) were prepared and characterized via scanning electron microscopy, scanning electron microscopy-energy dispersive X-ray (SEM-EDX), high-resolution transmission electron microscopy (HRTEM), and zeta potential analysis. Their cytotoxicity was assessed using immortalized human keratinocytes (HaCaT) cells at three different timepoints, and antibacterial activity was assessed using Gram-positive Methicillin resistant Staphylococcus aureus, MRSA, and Gram-negative neuro-pathogenic Escherichia coli K1 (E. coli K1) in vitro. The nanomaterials and composites displayed potent antibacterial effects against both types of bacteria and low cytotoxicity against HaCaT cells at 200 μg mL−1, which is promising for their utilization for biomedical applications.